Contemporary Comparative Politics and Revival of Regime Analysis Contra Reviving Aristotle’s Regime Science - Bates, Clifford A. Jr. (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
This paper suggests that upon comparing the various behavioural models and post-behavioural approaches (mostly understood as “the return of the state” and the concept of the political regime that emerges from that return) to compare political systems, we discover that Aristotle’s science of regimes is a superior framework to various models advanced by the majority of regime frameworks of contemporary comparative political science. In examining that whole attempt to recover the regime as a means to analyze human political behaviour one finally comes to see that Aristotle’s approach allows a more accurate and precise presentation of human political behaviour found within the structure of given political communities that are shaped by the given form of a particular regime.

W artykule zasugerowano, że porównanie różnych modeli behawioralnych i podejścia post-behawioralnego (rozumianego przede wszystkim jako „powrót państwa” i pojęcie reżimu politycznego, będące wynikiem tego powrotu) w celu porównania systemów politycznych prowadzi do wniosku, że arystotelesowska nauka o reżimie jest nadrzędnym punktem odniesienia dla rozmaitych modeli większości koncepcji reżimu opracowanych w ramach współczesnej politologii porównawczej. Badając wszystkie te próby zmierzające do odrodzenia koncepcji reżimu jako instrumentu analizy zachowań politycznych człowieka dostrzega się, że podejście przyjęte przez Arystotelesa pozwala na celniejsze i dokładniejsze przedstawienie zachowań politycznych występujących w strukturze określonych społeczności politycznych kształtowanych według danego reżimu.
Współczesna polityka porównawcza i odrodzenie analizy reżimu a odrodzenie arystotelesowskiej nauki o reżimie
Keywords: Aristotle’s politics; comparative politics; regime(s); political system(s); behaviouralism; polityka Arystotelesa; polityka porównawcza; reżim(y); system(y) polityczny/e; behawioralizm